KONSEKUENSI PENILAIAN PERUSAHAAN: STUDI EMPIRIS DAMPAK KINERJA KEUANGAN PADA PERUSAHAAN TAMBANG DI BEI - Asni, Nur; Lestari, Kurnia Cahya (Universitas Muhammadiyah Jember, 2024)
This study aims to determine how stock prices represent the company's valuation as a consequence of the company's financial performance in mining companies listed on the Indonesia Stock Exchange (IDX). The research design used is quantitative research using secondary data obtained from the company's annual publication report and other reports relevant to this study. Annual publication reports can be accessed both on the Indonesia Stock Exchange website (https://www.idx.co.id/) and on the official website of each company. Population data of public mining companies is obtained through the Osiris database. Based on the search results, it is known that the number of public mining companies on the IDX is 30 companies. Furthermore, the number of companies that can be analyzed is 20, considering that all the required data is available in the 2019-2022 period. The data analysis used is panel data regression analysis using the Stata 13 application. The panel data test results show that ROA and working capital have a positive and significant effect on stock prices, while company growth has no impact on stock prices. The results of this study provide theoretical implications related to positive signals from investors on the company's ability to generate profits and efficient working capital management for the benefit of investors and other parties related to the company